The CJEU likes to blame loudly and to applaud quietly: the co-respondent mechanism in the light of opinion 2/13. Issue 1 (February 2017) - Korenica, Fisnik; Doli, Dren
The Draft Accession Agreement (DAA) for the EU's accession to the ECHR has been found to be incompatible with the EU Treaties by the Court of Justice of the European Union (CJEU). One of the grounds on which the CJEU condemned the Agreement was the design of the co-respondent mechanism. The issue of attributing responsibility to the EU and its Member States for joint violations of the ECHR has been central to the legal debate over the EU's accession to the ECHR. To this end, this article examines the co-respondent mechanism in light of the findings in Opinion 2/13, considering each of its claims regarding the modes for triggering the co-respondent procedure, the concerns on the joint-responsibility model and the assumed loopholes on the possibility that one of the (co-)respondent(s) withdraw from the procedure before the European Court of Human Rights. The article also presents an analysis to the question of whether the CJEU was right to reject the core provisions of the co-respondent mechanism established by the DAA.